A Birth Cohort Study on the Genetic Modification of the Association of Prenatal Methylmercury With Child Cognitive Development. Issue 10 (26th June 2019) - Julvez, Jordi; Davey Smith, George; Ring, Susan; Grandjean, Philippe
Abstract: Genetic predisposition might affect neurodevelopmental outcomes of prenatal methylmercury exposure. We examined suspected heterogeneities for modification of exposure-related neurodevelopment in children from the Avon Longitudinal Study of Parents and Children (1991–2000), Bristol, United Kingdom. A subgroup ( n = 1, 127 from a pilot study and 1, 045 from the present study) was identified based on the availability of the mercury concentration of cord tissue as a measure of prenatal methylmercury exposure, data on 247 single-nucleotide polymorphisms (SNPs), and Wechsler Intelligence Scale for Children intelligence quotient (IQ) scores. Log10 -transformed mercury concentration was positively associated with IQ, but adjustment for confounding cofactors attenuated this association. A finding of enhanced interaction with methylmercury was replicated in this study for the minor allele of rs1042838 (progesterone receptor) (β = −11.8, 95% confidence interval: −23.0, −0.6; P for interaction = 0.004) and weakly for rs662 (paraoxonase 1) (β = −3.6, 95% confidence interval: −11.4, 4.3; P = 0.117). In the joint sample, new interacting single-nucleotide polymorphisms were discovered in relation to superoxide dismutase 2, ATP binding cassette subfamily A member 1, and metallothionein 1M genes. While the low-level prenatal exposure to methylmercury was not associated with child cognition, progesterone receptor rs1042838 minor alleles revealed a negative association of mercury exposure with IQ.